Functional characterization of a novel CSF1R mutation causing hereditary diffuse leukoencephalopathy with spheroids. Issue 4 (6th February 2019) - Kraya, Torsten; Quandt, Dagmar; Pfirrmann, Thorsten; Kindermann, Andrea; Lampe, Leonie; Schroeter, Matthias L.; Kohlhase, Jürgen; Stoevesandt, Dietrich; Hoffmann, Katrin; Villavicencio‐Lorini, Pablo
Abstract: Background: Colony‐stimulating factor 1 receptor is a tyrosine kinase transmembrane protein that mediates proliferation, differentiation, and survival of monocytes/macrophages and microglia. CSF1R gene mutations cause hereditary diffuse leukoencephalopathy with spheroids (HDLS), an autosomal‐dominantly inherited microgliopathy, leading to early onset dementia with high lethality. Methods: By interdisciplinary assessment of a complex neuropsychiatric condition in a 44‐year old female patient, we narrowed down the genetic diagnostic to CSF1R gene sequencing. Flow cytometric analyses of uncultivated peripheral blood monocytes were conducted sequentially to measure the cell surface CSF1 receptor and autophosphorylation levels. Monocyte subpopulations were monitored during disease progression. Results: We identified a novel heterozygous deletion–insertion mutation c.2527_2530delinsGGCA, p.(Ile843_Leu844delinsGlyIle) in our patient with initial signs of HDLS. Marginally elevated cell surface CSF1 receptor levels with increased Tyr723 autophosphorylation suggest an enhanced receptor activity. Furthermore, we observed a shift in monocyte subpopulations during disease course. Conclusion: Our data indicate a mutation‐related CSF1R gain‐of‐function, accompanied by an altered composition of the peripheral innate immune cells in our patient with HDLS. Since pharmacological targeting of CSF1R with tyrosine kinase inhibitors prevents disease progression in mouse models of neurodegenerative disorders, a potential pharmacological benefit of CSF1R inhibition remains to be elucidated for patients with HDLS. Abstract : In this study, we characterize the functional relevance of a novel CSF1R mutation identified in a patient with typical manifestation and progression of hereditary diffuse leukoencephalopathy with spheroids (HDLS), an early onset and severe neurodegenerative disease. Using primary innate immune cells our functional studies indicate rather a gain‐of‐function than a loss‐of‐function, as described previously in transfected cell lines, regarding the mutation‐related CSF1 receptor activity. Another new aspect that could be relevant to understand HDLS pathogenesis is an observed shift of subpopulations of the peripheral innate immune cells during disease course.